Histone chaperone FACT complex inhibitor CBL0137 interferes with DNA damage repair and enhances sensitivity of medulloblastoma to chemotherapy and radiation. (1st November 2021) - Song, Heyu; Xi, Shaoyan; Chen, Yingling; Pramanik, Suravi; Zeng, Jiping; Roychoudhury, Shrabasti; Harris, Hannah; Akbar, Anum; Elhag, Salma S.; Coulter, Donald W.; Ray, Sutapa; Bhakat, Kishor K.
Abstract: Medulloblastoma (MB) is a malignant pediatric brain tumor with a poor prognosis. Post-surgical radiation and cisplatin-based chemotherapy have been a mainstay of treatment, which often leads to substantial neurocognitive impairments and morbidity, highlighting the need for a novel therapeutic target to enhance the sensitivity of MB tumors to cytotoxic therapies. We performed a comprehensive study using a cohort of 71 MB patients' samples and pediatric MB cell lines and found that MB tumors have elevated levels of nucleosome remodeling FACT (FAcilitates Chromatin Transcription) complex and DNA repair enzyme AP-endonuclease1 (APE1). FACT interacts with APE1 and facilitates recruitment and acetylation of APE1 to promote repair of radiation and cisplatin-induced DNA damage. Further, levels of FACT and acetylated APE1 both are correlate strongly with MB patients' survival. Targeting FACT complex with CBL0137 inhibits DNA repair and alters expression of a subset of genes, and significantly improves the potency of cisplatin and radiation in vitro and in MB xenograft. Notably, combination of CBL0137 and cisplatin significantly suppressed MB tumor growth in an intracranial orthotopic xenograft model. We conclude that FACT complex promotes chemo-radiation resistance in MB, and FACT inhibitor CBL0137 can be used as a chemo-radiation sensitizer to augment treatment efficacy and reduce therapy-related toxicity in high-risk pediatric patients. Highlights: FACT complex facilitates the binding and acetylation of APE1 at damage sites in chromatin and promotes drug resistance. Elevated levels of AcAPE1 and FACT complex are associated with poor prognosis in MB. FACT inhibitor CBL0137 improves the potency of cisplatin and radiation in MB.